Improving Performance and Safety of Lithium Metal Batteries Through Surface Pretreatment Strategies - Gyuri Youk; Jeongmin Kim; Oh B. Chae (Energies)
Lithium metal batteries (LMBs) are promising candidates for electric vehicles (EVs) and next-generation energy storage systems owing to their high energy densities. The solid electrolyte interphase (SEI) on the Li metal anode plays an important role in influencing the Li deposition form and the cycle life of the LMB. However, the SEI on Li metal differs from that for other anodes, such as graphite, owing to its instability and reactivity. In addition, dendrite growth has hindered the commercial application of Li metal batteries in regular portable electronics to EVs. This review summarizes SEI formation on Li metal, dendrite formation and growth, and their impact on battery performance. In addition, we reviewed the recent progress in pretreatment strategies using materials such as polymers, carbon materials, and inorganic compounds to suppress dendritic growth.